(untitled) (Pakistan Journal of Science, 2022)
The formulation and solution of aircraft attacking problem, having supply of fuel and aircrafts availability constraints was determined. Softset theory and statistical approaches were used for air craft selection and probability of destruction respectively. The pattern search methods were used for the optimization of aircraft attacking problem. These methods were essentially intended for unconstrained optimization problems. In formulated aircraft attacking problem the constraints were controlled by using exterior penalty functions. MATLAB environment was used to calculate the results of the aircraft attacking problem, which exhibited the efficiency of methods. Comparative study was also provided for the best selection of these pattern search methods. Finally it was concluded that the probability of failure was 0.0000013 to demolish the targets. Numerical results witnessed the remarkable low computational cost behavior of Hooke and Jeeve,s method which was the best one.